Peran Moderasi Ukuran Perusahaan Terhadap Faktor-Faktor Yang Mempengaruhi Islamic Social Reporting - Desy Dwi Ayu Lestari; Mochlasin Mochlasin (LPPM ISNJ Bengkalis, 2021)
Disclosure of Islamic Social Reporting (ISR) has a role in the company, and the broad ISR will lead the company to a positive impact. This study aims to analyze the effect of profitability, leverage, and institutional ownership on Islamic Social Reporting (ISR) disclosure with firm size as a moderating variable in companies listed on the Jakarta Islamic Index (JII) for the 2014-2019 period. Determination of the sample using the purposive sampling method. The data used are 84 company annual reports. The test analysis method uses Moderated Regression Analysis (MRA). The study results partially show that profitability, leverage, and institutional ownership do not affect ISR disclosure. Firm size can moderate the effect of leverage on ISR disclosure. Meanwhile, firm size cannot moderate the effect of profitability and institutional ownership on ISR disclosure. Companies with declining or increasing financial conditions cannot motivate companies to make more comprehensive disclosures. Companies with good intentions, of course, will continue to make broader disclosures in financial conditions up or down.